Actualization of Productivity and Independence Values in the Hadith of the Prophet: A Thematic Analysis of Islamic Work Ethics - Purwantoro (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2025)
This study aims to examine Islamic work ethics through an analysis of three key hadiths of Prophet Muhammad Sallaawahu ‘Alayhi Wasallam related to faith-driven productivity, purposeful action, and independent labor. The core issue addressed is the weak internalization of work values among contemporary Muslims, who often reduce religion to ritual practices alone. Using a qualitative approach and content analysis method, the selected hadiths are analyzed in terms of their chains of transmission (sanad), textual content (matan), and contextual relevance to Muslim work behavior. The results reveal that these three hadiths collectively offer a coherent framework for Islamic work ethics that balances spiritual motivation, time efficiency, and economic self-reliance. This study concludes that work in Islam is not merely an economic endeavor but a form of moral responsibility and social worship oriented toward barakah (blessing) and societal benefit.